Detection of Mercury Ions in Water using a Plastic Optical Fiber Sensor - Hardiantho, Willy; Arminah, Bidayatul; Arifin, Arifin (Universitas Mataram, 2021)
Research has been carried out on the detection of mercury ions in water using plastic optical fibers. Detection of mercury ions is done by immersing the optical fiber sensor in the HgCl2 solution, where both ends of the sensor are connected to an LED and a phototransistor. LED as a light source will emit light along with the optical fiber which will be received by the phototransistor. The optical light received by the phototransistor is converted into an electric voltage and given a gain in the differential amplifier. The output voltage in the form of an analog signal is converted into a digital signal on the Arduino UNO so that it can be read on a computer. The optical fiber as a sensor is made in two configurations, namely U configuration and spiral spring configuration. The jacket and the fiber optic cladding are peeled off and then covered with chitosan. Each configuration will be given a variation of the curve to analyze the characteristics of the sensor. The curvature can cause a large power loss resulting in attenuation of the light intensity of the LED received by the phototransistor. Apart from the effect of indentation on optical fibers, the output voltage measurement results are also influenced by the level of HgCl2 concentration. The best measurement results for mercury ion sensors in water using plastic optical fibers are obtained in a spiral spring configuration with a chitosan cladding with a variation of 6 coils which has a sensitivity of 104.065 mV/ppm.